Role of microRNAs and long‐non‐coding RNAs in CD4+ T‐cell differentiation. Issue 1 (2nd April 2013) - Pagani, Massimiliano; Rossetti, Grazisa; Panzeri, Ilaria; de Candia, Paola; Bonnal, Raoul J. P.; Rossi, Riccardo L.; Geginat, Jens; Abrignani, Sergio
Summary: CD4 + T lymphocytes orchestrate adaptive immune responses by differentiating into various subsets of effector T cells such as T‐helper 1 (Th1), Th2, Th17, and regulatory T cells. These subsets have been generally described by master transcription factors that dictate the expression of cytokines and receptors, which ultimately define lymphocyte effector functions. However, the view of T‐lymphocyte subsets as stable and terminally differentiated lineages has been challenged by increasing evidence of functional plasticity within CD4 + T‐cell subsets, which implies flexible programming of effector functions depending on time and space of T‐cell activation. An outstanding question with broad basic and traslational implications relates to the mechanisms, besides transcriptional regulation, which define the plasticity of effector functions. In this study, we discuss the emerging role of regulatory non‐coding RNAs in T‐cell differentiation and plasticity. Not only microRNAs have been proven to be important for CD4 + T‐cell differentiation, but it is also likely that the overall T‐cell functioning is the result of a multilayered network composed by coding RNAs as well as by short and long non‐coding RNAs. The integrated study of all the nodes of this network will provide a comprehensive view of the molecular mechanisms underlying T‐cell functions in health and disease.